1998
DOI: 10.1038/eye.1998.239
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma screening by optometrists: Positive predictive value of visual field testing

Abstract: Visual field testing is currently leading to unnecessary referrals to the hospital eye service with no detectable improvement in the accuracy of glaucoma suspect referrals. It is important that optometrists perform visual field testing in accordance with validated screening methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
30
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 19 publications
3
30
0
Order By: Relevance
“…2,4,5 Up to 12% of optometrist referrals were made for isolated VF loss in the absence of any glaucoma damage. 7,8 A separate study reported an increase in false-positive referrals from 1988 to 1993, and this was felt to be due to the increase in VF testing and to an increased willingness to refer patients at lower IOPs. 6 As referrals have been shown to be more accurate when IOP measurement, VF testing, and optic disc assessment were all performed, 2,3 it was important that any glaucoma detection programme involving optometrists should involve all three parameters.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5 Up to 12% of optometrist referrals were made for isolated VF loss in the absence of any glaucoma damage. 7,8 A separate study reported an increase in false-positive referrals from 1988 to 1993, and this was felt to be due to the increase in VF testing and to an increased willingness to refer patients at lower IOPs. 6 As referrals have been shown to be more accurate when IOP measurement, VF testing, and optic disc assessment were all performed, 2,3 it was important that any glaucoma detection programme involving optometrists should involve all three parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Using a combination of all three investigations has been shown to have the highest positive predictive value (Bell and O'Brien, 1997;Newman et al, 1998;Harper and Reeves, 1999;Theodossiades and Murdoch, 1999). Glaucoma referrals pose a problem as highlighted in a recent audit (Vernon and Ghosh, 2001), which found that locally agreed guidelines for referral did not improve the true positive referral rate for glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…There is no formal screening programme for glaucoma in the UK, so detection is largely dependent on the public attending an optometrist for sight testing, with optometrists responsible for over 90% of referrals to the Hospital Eye Service. [5][6][7][8] Three tests/examinations are recommended for the detection of glaucoma; measurement of IOP, visual field and optic disc assessment. However, optometrist case-finding and referral criteria vary considerably across the profession.…”
mentioning
confidence: 99%
“…11 Recent studies have reported positive predictive values (PPV) of optometrist referrals for glaucoma ranging between 0.31 and 0.50. 5,7,9,[11][12][13][14] As PPV is directly related to prevalence and prevalence is low, this figure implies that optometrist referrals have a high degree of specificity. 15 The proportion of undetected glaucoma in the developed world, however, remains at about 50%.…”
mentioning
confidence: 99%